TRADITIONAL KNOWLEDGE VERSUS INTELLECTUAL PROPERTY RIGHTS PROTECTION: A CASE STUDY OF GIRILAYU BATIK VILLAGE, INDONESIA - Adi, Yustia Atsanatrilova; Wijaya, Mahendra; Pujihartati, Sri Hilmi; Sudarsana, Sudarsana (Cepalo, 2026)
This study analyzes the social barriers preventing artisans in Girilayu Batik Village, Central Java, from securing Intellectual Property Rights (IPR) protection for traditional batik knowledge. Using a qualitative approach with purposive sampling and in-depth interviews with seven key informants conducted between June and August 2024, the study identifies three main constraints: the absence of a collective artisan identity required for legal classification and representation, the incompatibility of oral knowledge transmission with formal IPR requirements, and the lack of unified institutional structures for registration. Drawing on Bourdieu’s framework, the findings show that fragmented habitus and weak social capital hinder the transformation of embodied cultural capital into institutionalized legal protection. The study demonstrates structural incompatibilities between existing IPR laws and traditional knowledge systems and underscores the need for sui generis legislation that accommodates collective ownership, oral transmission, and cultural significance.